An introduction to indonesian law - Peter mahmud marzuki (Setera Press, 2011)
Constitution is implemented by laws both written and unwritten law. Whatever the form of law would be, it must be honored; otherwise, the society leads to chaos. In this book, law does not necessarily mean written law. It is Professor Marzuqi's stance that he is not positivist; in this book, therefore, he also refers to custom and practices, which he regards as law too. This book begins with the history of Indonesian law. It is a good point of departure because presenting pre independence legal sys- tem, he describes how pluralistic and discriminative the legal system under the Netherlands-Indie administration. It is interesting that he retains the original Dutch legal terms and translated into English, by which the reader may conceive the original meaning of the terms. In addition, in this chapter, he shows plainly how the 1945 Constitution was prepared and from his description, it is known that the constitution was intended to be a temporary or provisional constitution.